Disparities in health and health care in Myanmar - Zaw, Phyu Phyu Thin; Htoo, Thant Sin; Pham, Ngoc Minh; Eggleston, Karen (The Lancet (British edition), 2015)
Myanmar (Burma) is undergoing a complex political and economic transformation, from a long civil war and military regime to a peace process and democratisation. Since 2011, the Myanmar Ministry of Health has started to rehabilitate the fragile health system, setting the goal of achieving universal health coverage by 2030.1 To achieve this target, Myanmar will have to face substantial challenges; arguably one of the most important difficulties is how to allocate limited health-care resources equitably and effectively.